Brucella abortus-infected B cells induce osteoclastogenesis - Pesce Viglietti, Ayelén Ivana (2016)
Brucella abortus is an intracellular bacterium that establishes lifelong infections in livestock and humans although the mechanisms of its chronicity are poorly understood. Activated B cells have long lifespan and B. abortus infection activates B cells. Our results indicate that the direct infection of B cells with B. abortus induced matrix metalloproteinase-9 (MMP-9), receptor activator for NF κB ligand (RANKL), tumor necrosis factor (TNF)-α and interleukin (IL)-6 secretion. In addition, supernatants from B. abortus-infected B cells induced bone marrow-derived monocytes to undergo osteoclastogenesis. Using osteoprotegerin, RANKL's decoy receptor, we determined that RANKL is involved in osteoclastogenesis induced by supernatants from B. abortus-infected B cells. The results presented here shed light on how the interactions of B. abortus with B cells may have a role in the pathogenesis of brucellar osteoarticular disease.